2009
DOI: 10.4319/lom.2009.7.391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the triplet state photoreactivity of dissolved organic matter isolated by chromatography and ultrafiltration using an alkylphenol probe molecule

Abstract: The triplet state photochemistry of dissolved organic matter (DOM) isolated by XAD and C-18 chromatography and tangential flow ultrafiltration (TFUF) was investigated using 2,4,6 trimethylphenol (TMP) as a molecular probe. Water samples were taken from an Arctic seep adjacent the Oksrukuyik River (OKS) on the north slope of Alaska, USA, where DOM is derived primarily from allochthonous material and from a eutrophic midlatitude wetland, Old Woman Creek (OWC), in northern Ohio, USA, where the DOM is formed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…Although many past studies of DOM photoreactivity have been conducted using isolates, it is not clear whether the photoreactivity of solutions prepared with isolates is truly representative of whole water samples, 43,44 particularly those with effluent contributions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although many past studies of DOM photoreactivity have been conducted using isolates, it is not clear whether the photoreactivity of solutions prepared with isolates is truly representative of whole water samples, 43,44 particularly those with effluent contributions.…”
Section: Introductionmentioning
confidence: 98%
“…In this work, we also compared the formation of 3 OM* and 1 O 2 between whole water samples and solutions prepared with organic matter isolates obtained from aliquots of the same water. Quantum yields are commonly measured using isolated DOM due to its stability and the overall convenience of this approach 44. Solutions prepared from paired OM isolates collected upstream and downstream of each WWTP showed little differences in f TMP and Φ 1O2 values (Figure 2), as was the case for whole water samples.…”
mentioning
confidence: 98%
“…As such allochthonous DOM precursors contain significant amounts of lignins and are characterized by high levels of aromaticity. In our previous studies we demonstrated that allochthonous DOM is effective at generating ROS such as the hydroxyl radical (OH•), while autochthonous organic matter is effective at forming 3 DOM (Guerard et al, 2009;Cawley et al, 2009). Subsequent research by Wenk et al (2011Wenk et al ( , 2012 demonstrated that the presence of unknown anti-oxidant moieties (presumably phenolic compounds) present in allochthonous DOM (and much less prevalent in autochthonous DOM) maybe responsible for this dichotomy in DOM photo-reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive species (RS) measured in the present study include: hydroxyl radicals (•OH), singlet oxygen (¹O₂) and excited triplet states of dissolved organic matter (³DOM*) using the following probe: benzene (Balakrishnan et al, 1970;Warneck et al, 1988), Furfuryl alcohol (FFA) (Haag et al,1984a;1984b) and 2,4,6-trimethylphenol (TMP) (Cawley et al, 2009;Rosado-Lausell et al, 2013), respectively.…”
Section: Reactive Species Measurementmentioning
confidence: 99%
“…The methyl groups on TMP act as electron donors to the conjugated ring, which stabilizes the TMP cation after oxidation by ³DOM (Cawley et al, 2009). …”
Section: Benzene Serves As a Common Probe For Hydroxyl Radicals (•Oh)mentioning
confidence: 99%